LITERATURE REVIEW OF LEADERSHIP AND THE DYNAMICS OF HUMAN RESOURCE MANAGEMENT - Purba, Mercidominick Fidelius Conrad Menachem (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study reviews leadership dynamics in human resource management, focusing on how leadership styles affect employee performance, job satisfaction, and organizational commitment. A systematic review of 16 peer-reviewed articles (2020–2025) was conducted, using a thematic analysis approach. Findings show that transformational, ethical, and adaptive leadership enhance performance and commitment, while authoritarian and abusive styles lead to reduced motivation and counterproductive behaviors. Moderating factors such as organizational ethical climate and power distance, as well as individual traits like proactive personality, influence these relationships. This review offers insights for developing inclusive and adaptive leadership models to improve organizational outcomes.